MAPPING POTENTIAL TECHNOLOGY APPROPRIATE SMALL AND MEDIUM ENTERPRISES AS EFFORTS TO IMPROVE TECHNOLOGY PREPARATION LEADERSHIP IN REGION OF PONOROGO - Rochmat Aldy Purnomo; Titin Eka Ardiana (Trunojoyo University of Madura, 2017)
Research Objectives